Childbirth resulting in traumatic stretching and prolapsing of the anterior lip of the cervix outside the vagina: A case report - Ogbonnaya Orji; Nnabuike Chibuoke Ngene (Elsevier, 2022)
Background: We report on childbirth trauma resulting in a rare stretching and prolapsing of the anterior lip of the cervix beyond the vaginal introitus, and describe the management. Case Presentation: A 17-year-old primigravida who had normal antenatal care delivered a live normal male baby weighing 3600 g at 39 weeks of gestation. The patient sustained a birth trauma resulting in the anterior lip of the cervix becoming stretched and prolapsing outside the vagina. There was an associated uterovaginal prolapse (Pelvic Organ Prolapse Quantification System grade 2). The prolapse of the cervix recurred after the initial repositioning of the cervix into the vagina. Subsequently, a vaginal ring pessary was applied to reduce the uterus and cervix. The most distal part of the prolapsed cervix was necrotic, remained outside the vagina despite the application of the ring pessary, and was excised. The use of the ring pessary was discontinued at 6 weeks postpartum, the cervix healed without obvious defect, and there was no prolapse at 3-month follow-up. Conclusion: A stretched cervix that prolapses beyond the vaginal introitus and uterovaginal prolapse are rare complications of childbirth that may be amenable to treatment with a ring pessary and to surgical excision of non-viable cervical tissue.